Trauma on duty: cognitive functioning in police officers with and without posttraumatic stress disorder (PTSD) - Alexandra Bisson Desrochers (Taylor & Francis Group, 2021)
Background Neuropsychological alterations co-occur with Posttraumatic Stress Disorder (PTSD); yet, the nature and magnitude of such alterations in police officers remains unknown despite their high level of trauma exposure. Objective The current research sought to examine (1) cognitive functioning among police officers with and without PTSD; (2) the clinical significance of their cognitive performance; and (3) the relationship between PTSD symptoms and cognition. Method Thirty-one police officers with PTSD were compared to thirty age- and sex-matched trauma-exposed officers without PTSD. Clinical assessment and self-report questionnaires established PTSD status. All participants underwent a neuropsychological evaluation. Results Police officers with PTSD displayed lower cognitive performance across several domains, notably executive functioning, verbal learning and memory, and lexical access, compared to controls. The neuropsychological decrements in the PTSD group were mild compared to normative data, with average performances falling within normal limits. Among officers with PTSD, higher levels of intrusion symptoms were associated with reduced efficacy in executive functioning, as well as attention and working memory. Moreover, increased intrusion and avoidance symptoms were associated with slower information processing speed. Conclusion Considering that even mild subclinical cognitive difficulties may affect their social and occupational functioning, it appears important to integrate neuropsychological assessments in the clinical management of police officers diagnosed with PTSD.